Photophysical properties of self-aggregated porphyrin: semiconductor nanoassemblies - E. Zenkevich; T. Blaudeck; M. Abdel-Mottaleb; F. Cichos; A. Shulga; C. von Borczyskowski (International Journal of Photoenergy, 2006)
Colloidal semiconductor nanocrystals from CdSe show photoluminescence quenching via titration with porphyrin derivatives. This quenching is an indication of the formation of nanoassemblies via surface attachment of pyridyl linker groups. As a consequence of the complex formation, dynamic and/or static interactions between QD and porphyrins are induced. Quenching efficiencies depend critically on sample stability, temperature, solvent, and electronic properties of the porphyrins. In order to optimize photoinduced dynamic processes these parameters have to be under control.